The correlation between scientific argumentation with viruses learning outcomes of senior high school student - V Vera; Yenny Anwar; E Ermayanti (Biosfer: Jurnal Pendidikan Biologi, 2021)
This study aims to determine the correlation between ability of scientific argumentation and learning outcomes of students on the virus topic with the research subjects were X IPA students in SMA Negeri 1 Indralaya Utara 2018/2019 (n = 47). This type of research is quantitative descriptive with the correlation method. This study used two data collection techniques is written test and observation. The result showed that students learning was 49% very good, 15% good, 17% sufficient, and 19% less. The results of writing scientific argumentation of students are 9% excellent, 11% good, 21% sufficient, 26% less, and 33% very poor. The average scientific argumentation of students based on Toulmin's Argument Pattern (TAP) is 100% of students able to submit a claim, 5% able to submit data, 77% able to convey a warrant, 6% able to convey backing, 7% able to convey rebuttal and 3% able to convey qualifer with the quality of scientific argumentation in general at level 2. The results of the correlation test of scientific argumentation include writing argumentation and TAP with learning outcomes is 0,311 it is means a low correlation. Based on the results showed a correlation between the ability of scientific argumentation with learning outcomes of class x students in SMA Negeri 1 Indralaya Utara